Keanekaragaman dan Status Konservasi Burung di Kawasan Gili Meno, Lombok Utara - Vivi Wardhani; I Wayan Suana; Gito Hadiprayitno (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The presence of birds in Gili Meno has a positive impact on environmental aspects as birds serve as bioindicators of environmental quality, pest controllers, and aid in pollination processes. Based on research conducted in 2010, 2011, 2012, and 2015, there has been an increase in bird populations in the Gili Meno area, particularly birds from the Ardeidae family. With rapid development currently underway, it is suspected to affect the presence of birds in Gili Meno, necessitating monitoring of bird diversity and conservation status in the area. This study aims to assess the diversity and conservation status of birds in the Gili Meno area. The research was conducted on Gili Meno from May to June 2022. Data collection utilized snowball sampling for interviews and transect methods combined with point counts. Observational data were analyzed using the Shannon-Wiener diversity index. The results indicate a total of 29 bird species found in the Gili Meno area, belonging to 22 families, with a diversity index of 2.8. The conservation status of most birds (97%) in the Gili Meno area is categorized as "least concern" according to IUCN criteria and classified as "unprotected" species under P.106/MENLHK/Setjen/Kum.1/12/2018. Acridotheres javanicus is listed as vulnerable by IUCN, while Thallaseus bergii is protected under P.106/MENLHK/Setjen/Kum.1/12/2018.